2012
DOI: 10.3748/wjg.v18.i11.1216
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of gastric cancer and immunoblot validation of potential biomarkers

Abstract: This work presents a set of possible diagnostic biomarkers, validated for the first time. It might contribute to the efforts of understanding gastric cancer carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 98 publications
2
16
0
Order By: Relevance
“…TALDO catalyzes the reversible transfer of a three-carbon unit between various sugar phosphates (from ketose to aldose sugar phosphates) (10). A previous study has revealed that TALDO is significantly overexpressed in gastric adenocarcinoma (41). Furthermore, its expression is associated with metastatic behavior in HCC (42).…”
Section: Roles Of Ribose-5-phosphate Isomerase (Rpi) and Ribulose-5-pmentioning
confidence: 99%
“…TALDO catalyzes the reversible transfer of a three-carbon unit between various sugar phosphates (from ketose to aldose sugar phosphates) (10). A previous study has revealed that TALDO is significantly overexpressed in gastric adenocarcinoma (41). Furthermore, its expression is associated with metastatic behavior in HCC (42).…”
Section: Roles Of Ribose-5-phosphate Isomerase (Rpi) and Ribulose-5-pmentioning
confidence: 99%
“…We first separated the proteins in an alkaline pH using the conventional procedures that were used in our previous study (in‐gel rehydration, conventional rehydration solution, DTT as reducing agent; see Supporting Information Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we report on a detailed investigation of gastric tissue samples using 2DE under alkaline conditions. To complement our previous data from the analysis in the acidic pH range , the same samples and detection techniques were used. As 2DE specifically designed for alkaline pHs has not been reported previously for gastric cancer, we first optimized the procedures for this specific purpose.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated tumour markers are known to be associated with the higher probability of lymph node metastases, lymphatic and blood vessel invasion, depth of invasion, higher stage and dissemination of the disease. Kočevar et al 57 reported that translationally controlled tumour protein (TPT1) was shown to be differentially expressed only in patients GEJ cancer, but, it clinical have to be established.…”
Section: Discussionmentioning
confidence: 99%